Development of Learning Media for Listening Skills of German Language Based on Web DaF (Deutsch als Fremdsprache) for Students High School in Makassar - Laelah Azizah; Wahyu Kurniati Asri; Misnah Mannahali (Makassar State University, 2020)
This research aims to know the validity, practicality, and effectiveness of the DAF web-based media learning listening skills for high school students in Makassar City. The design of instructional media uses the Thiagarajan four D (4-D) model of development stages the which consists of four items, namely define, design, develop and develop. Data collection is done through validation of learning tools, observation, student questionnaire responses. The products produced in this study were lesson plans, teaching materials, and LKPD web-based learning daf listening skills. Based on the results of the analysis of the data it was concluded that the learning media for listening to the German language based on web DAF is valid, practical, and effective.